Pharmacokinetics and brain targeting of trans-resveratrol loaded mixed micelles in rats following intravenous administration. (15th March 2020) - Katekar, Roshan; Thombre, Ganeshkumar; Riyazuddin, Mohammed; Husain, Athar; Rani, Hiral; Praveena, Kusuma Sushma; Gayen, Jiaur R.
Abstract: Trans-Resveratrol (T-RES) is a compound with wide therapeutic applications that shows low bioavailability and distribution across blood-brain barrier. The purpose of our study was to develop T-RES loaded mixed micelle (T-RES-MM) for its enhanced systemic availability and targeting to the brain. T-RES-MMs were formulated using Pluronic F-127 (PF-127) and d-α-tocopheryl polyethylene glycol 1000 succinate (TPGS) by using film hydration process. Formulations were characterized for size of particles, zeta potential, drug efficiency of entrapment, drug loading, and hemolytic study. Further in vivo pharmacokinetic and brain distribution study carried out in Sprague Dawley rats. The nano ranged size for drug-loaded mixed micelles was 21.55 ± 2.15 nm for optimized formulation with PF-127:TPGS (4:1). Formulation with maximum drug loading and entrapment efficiency of 8.4 ± 0.37% and 94.37 ± 1.01% respectively were further used for in vivo study. Percent hemolysis by micelles at all concentrations indicates the biocompatibility and safety for administration by i.v. route. The AUC0-t for T-RES-MM was 460.98 ± 158.99 h*ng/ml while for T-RES it was 276.27 ± 174.05 h*ng/ml. Drug targeting index suggests successful targeting of T-RES to the brain. Overall findings conclude in prepared T-RES-MM exhibit superiority of formulation as compared to T-RES solution.